Analysis of Subsurface Layers using the Multichannel Analysis of Surface Waves Method in Manimbahoi, Gowa Regency: Analisis Lapisan Batuan Bawah Permukaan Menggunakan Metode Multichannel Analysis of Surface Waves di Manimbahoi Kabupaten Gowa - Muhammad Ikram Ramadhan; Muhammad Altin Massinai (JURNAL GEOCELEBES, 2022)
This research is about the structure of the soil layer at the research site in Manimbahoi, Parigi District, Gowa Regency. This research is very important considering that the location has experienced a mega landslide which resulted in some residents being not found. This study aims to provide an overview of the shallow soil layer at the landslide disaster location. This study uses one of the geophysical methods, Multichannel Analysis of Surface Waves (MASW) method, with 4 lines at points at the landslide location. Based on the results of the study, the velocity of the Vs30 wave was obtained in each line. On the first line the velocity of Vs30 is 303.5 m/s. On the second line the velocity of Vs30 is 284.1 m/s. On the third line the velocity of Vs30 is 309.0 m/s. On the fourth line the velocity of Vs30 is 256.1 m/s. Based on the soil classification by looking at the Vs30 velocity, it can be determined that the type of soil at the research location is medium soil (sand). Medium soil is unconsolidated sediment, described as soil composed of minerals that are not compact